Nanocápsulas de poli (L-ácido lático) contendo óleo de café torrado - Freiberger, Eliza Brito (2013)
Coffee flavor is a mixture of volatile components found in the oil obtained from the roasted coffee. Soluble coffee loses part of its aroma due to processing conditions which could be reintroduced to the product by the direct addition of the coffee oil. However, some studies point out difficulties in obtaining good results when working with in natura oil because of the high volatility and the flavor degradation. The incorporation of nanocapsules containing coffee oil could be an alternative to minimize these losses, because the encapsulating polymer could act as a protecting barrier and promote its controlled release. The aim of this work is obtain PLLA nanocapsules containing roasted coffee oil by the miniemulsification/solvent evaporation technique. The spectrophometric UV- Vis method used to quantify the coffee oil was validated. Formulations with different PLLA and oil concentrations and kind of surfactant were evaluated in respect to the average nanocapsules size and polydispersion index and oil recovery. All formulations demonstrated oil recovery values above 80 % demonstrating that the technique is adequate and can be consider a promising alternative to coffee oil nanocapsules production. Flavor analysis nanocapsules composition, which indicates the quality of the encapsulated oil, showed that the nanocapsules contain fractions of all the substances found on the in natura oil.